Post-Mining of Association Rules 2009
DOI: 10.4018/978-1-60566-404-0.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Semantics-Based Classification of Rule Interestingness Measures

Abstract: Assessing rules with interestingness measures is the cornerstone of successful applications of association rule discovery. However, as numerous measures may be found in the literature, choosing the measures to be applied for a given application is a difficult task. In this chapter, the authors present a novel and useful classification of interestingness measures according to three criteria: the subject, the scope, and the nature of the measure. These criteria seem essential to grasp the meaning of the measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Exponential development of semantic web, numerous linked data from social community, companies or end-users trigger new potential to connect and join data in order to share and reveal hidden relationship or "semantic association" [22]. Blanchard J. et al [18] studied in semantics-based classification of rule interestingness measures. The experiments showed that according to three criteria such as the subject, the scope, and the nature of the measure are novel and useful for classification of interestingness measures.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Exponential development of semantic web, numerous linked data from social community, companies or end-users trigger new potential to connect and join data in order to share and reveal hidden relationship or "semantic association" [22]. Blanchard J. et al [18] studied in semantics-based classification of rule interestingness measures. The experiments showed that according to three criteria such as the subject, the scope, and the nature of the measure are novel and useful for classification of interestingness measures.…”
Section: Related Workmentioning
confidence: 99%
“…Most existing methods [12], [13], [15]- [18] used real data for investigation and their techniques are clustering and correlation analysis with/without support-based pruning or table standardization. As a different approach, instead of real datasets, one of our previous works [19] investigated interestingness measures using a synthesis dataset but it is not systematic with a relatively small dataset.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation